AGEN HAYATI: KOMODITAS AGRIBISNIS DI ERA GLOBAL - Zamrodah, Yuhanin (JURNAL AGRI-TEK, 2015)
The purpose of this study was to study the potential biological agents as a commodity in the era of global agribusiness. The approach method is done with the study of literature, include: collecting data and information on the biological agent as a commodity agribusiness in the global era, the data obtained from scientific journals, seminar proceedings national, international, theses, and dissertations. Analysis of the data processed by descriptive qualitative. The results showed that biological agents have an important role in environmentally friendly OPT; Development can be done in a simple laboratory at the farm level so as to enable the development of agro-industries and businesses of biological agents in the group of farmers. Thus biological agents in the future will be used as a commodity in the era of global agribusiness. Keywords: Biological agents, OPT era of globalization